Resistenza e diritto pubblico - Cortese, Fulvio (Carte, Studi e Opere - Centro Trentin di Venezia, 2016)
What do the words Resistance and public law suggest? On the one hand, they evoke the close relationship between the Resistance, intended as a historical phenomenon, and the institutional solutions and legal problems which arose in that situation and which have soon given rise to a profound renewal of the state. On the other hand, they remind us of what happened, at a given moment, to many jurists, who were otherwise involved in the choice of the path to take, as scholars, public officials or as men. Moving from the evocation of Silvio Trentin's testimony, which functions here as an example, this volume suggests an interdisciplinary path, in which one can try to approach the complexity of the Resistance's legal universe, its many voices and its controversial representations. Seventy years after the Italian Republic's birth, wondering on such issues and remembering the experiences of some of their protagonists can provide a useful starting point to grasp a plural and very rich message, and to renew trust in a constituent legacy which is still capable of innervating the spirit of the country with strength.